The effect of IFRS adoption on accounting conservatism – New Zealand perspective - Zhang, Jian (Auckland University of Technology, 2011)
The impact of adopting International Financial Reporting Standards (IFRS) on earnings quality is intensively researched in recent years. This study investigates whether IFRS adoption has a positive effect on earnings quality proxied by accounting conservatism in New Zealand. The results suggest the existence of conditional conservatism for both pre- and post-adoption of IFRS. Furthermore, accounting conservatism is increased after the adoption of IFRS in New Zealand. Finally, accounting conservatism is improved for mandatory adopters but not for voluntary adopters after IFRS adoption. Thus, the overall findings suggest that the adoption of IFRS in New Zealand has a positive impact on earnings quality which stays in sharp contrast to the results of prior New Zealand studies/research.
Keywords: IFRS; Earnings quality; Accounting conservatism; Timely loss recognition; Voluntary adopters; Mandatory adopters; New Zealand